2018
DOI: 10.1159/000489149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LncRNA-HRIM Increases Cell Viability by Regulating Autophagy Levels During Hypoxia/Reoxygenation in Myocytes

Abstract: Backgrund/Aims: Ischemia reperfusion (I/R) promotes the severity of cardiomyocyte injury. Long noncoding RNAs (LncRNAs) are key regulators in cardiovascular diseases. However, the association between LncRNAs and myocardial I/R injury has not been thoroughly characterized to date. We attempted to clarify the potential biological role of a LncRNA (E230034O05Rik), which we named hypoxia/reoxygenation (H/R) injury-related factor in myocytes (HRIM), by investigating the differential expression of LncRNAs between gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Studies in rodent models have shown that I/R causes dysregulated lncRNA expressions in cardiac tissue. [10][11][12] For instance, Liu 11 with a similar trend of changes observed in both of the cell culture and the cardiac tissue. Collectively, these results support the notion that I/R causes a dysregulation of the expression of cardiac lncRNAs.…”
Section: Dys Reg Ul Ati On Of Lncrna E Xpre Ss Ions Following Myoc mentioning
confidence: 56%
See 2 more Smart Citations
“…Studies in rodent models have shown that I/R causes dysregulated lncRNA expressions in cardiac tissue. [10][11][12] For instance, Liu 11 with a similar trend of changes observed in both of the cell culture and the cardiac tissue. Collectively, these results support the notion that I/R causes a dysregulation of the expression of cardiac lncRNAs.…”
Section: Dys Reg Ul Ati On Of Lncrna E Xpre Ss Ions Following Myoc mentioning
confidence: 56%
“…Among these dysregulated lncRNAs, 12 have been confirmed to be related to genes encoding for apoptosis‐related proteins such as STAT3 and IL1R1 10 . Huang et al have explored the effect of I/R on lncRNA expressions inH9c2 myocytes and Langendorff‐perfused hearts from rats, showing that 797 lncRNAs and 1,898 mRNAs are differentially expressed after I/R challenge, 11 with a similar trend of changes observed in both of the cell culture and the cardiac tissue. Collectively, these results support the notion that I/R causes a dysregulation of the expression of cardiac lncRNAs.…”
Section: Dysregulation Of Lncrna Expressions Following Myocardial I/rmentioning
confidence: 94%
See 1 more Smart Citation
“…The global differential expression of lncRNAs analyzed by microarray analysis showed that 797 lncRNAs were differentially expressed in the H/R group. Therein, the repression lncRNA-HRIM via specific siRNAs protected cells from death through diminishing autophagy in H9c2 myocytes during H/R [ 80 ]. LncRNA NEAT1 associated with the development of various diseases was upregulated in peripheral blood and mouse cardiomyocytes during MI, which markedly increased the proliferation and migration of cardiomyocytes.…”
Section: Ncrnas Regulate Autophagy In Myocardial I/r-injurymentioning
confidence: 99%
“…HRIM silencing prevented death of cells by suppressing the autophagic activity in H/R-treated cells. However, the target genes of this lncRNA and the detailed mechanism of its autophagic effect need to be elucidated [42]. Other lncRNAs were highly expressed in diabetic murine heart and contributed to I/R injury by regulating autophagy.…”
Section: Macroautophagy Regulation By Noncoding Rnas During and Fomentioning
confidence: 99%